1994
DOI: 10.1007/bf02191890
|View full text |Cite
|
Sign up to set email alerts
|

The Zurich Study: XXIII. Epidemiology of headache syndromes in the Zurich cohort study of young adults

Abstract: This study examines the 1 year prevalence rates of headache syndromes in an epidemiologic cohort study of young adults ages 29-30 in Zurich, Switzerland. The 1 year prevalence rates of headache subtypes were 3.3% for migraine with aura and 21.3% of migraine without aura as defined by the International Headache Society (IHS) criteria. The demographic distribution, clinical features, sequelae, and treatment patterns of subjects with specific headache subtypes are described. The rates of migraine are compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
28
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
7
28
1
Order By: Relevance
“…Lipton et al found an overall 1-year prevalence rate of 18% and 7% in females and males, respectively, but in the age-group 30-39 years old, the prevalence was as high as 27% and 10%, respectively [5]. When comparing with age-specific prevalence rates, our results are in agreement with most previous findings [3][4][5][6][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 95%
“…Lipton et al found an overall 1-year prevalence rate of 18% and 7% in females and males, respectively, but in the age-group 30-39 years old, the prevalence was as high as 27% and 10%, respectively [5]. When comparing with age-specific prevalence rates, our results are in agreement with most previous findings [3][4][5][6][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 95%
“…The oneyear prevalence of headache ranged from 51% to 68% [15,16]. Epidemiological data on the prevalence of tensiontype headache have shown a range from 16% to 44.5% [15][16][17], of migraine from 10-25% [14,16,[18][19][20], and the prevalence of frequent headache has been estimated at 27% [21].…”
Section: Discussionmentioning
confidence: 98%
“…As there were altogether 1166 women, more than half of them without gainful occupation, and more or less able to wait at home for the end of a bad headache attack or a bad headache episode, the present reports are showing only part of this problem. Merikangas and co-workers [1] found up to 90% impairment of social and leisure activities, and up to 75% occupational impairment in the migraine sufferers among the high-risk group of the Zurich cohort study. According to the IHS criteria [5] and definitions the intensity of tension-type headache should not be severe, that is, not severe enough to block the usual daily activities.…”
Section: Impactmentioning
confidence: 95%
“…In a sizeable minority, disability occurred on more than 30 days per year: 11.3% of all patients, 13.4% of those with migraine and 7.6% of those with tension-type headache. These severe problems may be concentrated in the specialist clinic but they are closely related to the encroachment on the quality of life in the general population [1].…”
Section: Impactmentioning
confidence: 99%
See 1 more Smart Citation